Clinical Characteristics of Patients With IgG4-Related Disease Complicated by Hypocomplementemia - Fujita, Yuya; Fukui, Shoichi; Umeda, Masataka; Tsuji, Sosuke; Iwamoto, Naoki; Nakashima, Yoshikazu; Horai, Yoshiro; Suzuki, Takahisa; Okada, Akitomo; Aramaki, Toshiyuki; Ueki, Yukitaka; Mizokami, Akinari; et al. (Frontiers in Immunology, 2022)
Background: A proportion of patients with immunoglobulin (IgG) 4-related disease (IgG4-RD) have hypocomplementemia. We aimed to identify characteristics of such patients. Methods: We analyzed the demographic and clinical data and complement levels of 85 patients with IgG4-RD. We defined hypocomplementemia as serum C3 and/or C4 levels below the lower limit of normal at diagnosis. We also compared the characteristics of patients with and without IgG4-RD. Results: Thirty-two (38%) patients had hypocomplementemia at diagnosis. Patients with hypocomplementemia had more lymph node (p < 0.01), lung (p < 0.01), and kidney (p = 0.02) involvement and a higher IgG4-RD responder index than those without (p = 0.05). Additionally, patients with hypocomplementemia had significantly higher IgG (p < 0.01), IgG4 (p < 0.01), and soluble interleukin 2-receptor (sIL-2R) (p < 0.01) levels and total IgG minus IgG4 (p < 0.01). C3 and C4 levels negatively correlated with IgG, IgG4, and sIL-2R levels, total IgG minus IgG4, and number of IgG4-RD responder index: a measure of the disease activity in IgG4-RD. Patients with hypocomplementemia at diagnosis had a significantly higher frequency of relapse (p = 0.024), as determined using the log-rank test. A multivariate logistic regression analysis showed the presence of hypocomplementemia was independently associated with relapse (OR, 6.842; 95% confidence interval [95%CI], 1.684–27.79; p = 0.007). Conclusions: Patients with IgG4-RD with hypocomplementemia have a more active clinical phenotype, suggesting contributions of the complement system in the pathophysiology of IgG4-RD.